Fast and Inexpensive Synthesis of Multilayer Graphene Used as Pd Support in Alkaline Direct Ethanol Fuel Cell Anode - Souza, Felipe M.; Lima, Thays S.; Böhnstedt, Paula; Pinheiro, Victor S.; Batista, Bruno L.; Parreira, Luanna S.; Simões, Fábio R.; Codognoto, Lúcia; Hammer, Peter [UNESP]; Santos, Mauro C. (Springer Nature, 2021)
Multilayer graphene (G-US) and multilayer graphene muffled (Gm-US) produced by liquid exfoliation ultrasound were used as support for Pd nanoparticles with a load of 20 wt% for application in an alkaline direct ethanol fuel cell (ADEFC) anode. The multilayer graphene–based electrocatalyst (Pd/G-US) exhibited superior current density and less positive onset potential for ethanol oxidation reaction (EOR) than the commercial Pd/C (AA). Also, the Pd/G-US electrocatalyst showed the less positive onset potential for CO oxidation. In ADEFC experiments, the Pd/G-US catalyst exhibited a superior performance with 38 mW cm−2. The findings suggest that the defective graphene structure promotes electron transport, and the presence of oxygenated species increases hydrophilicity facilitating the oxidation of intermediates. Hence, the synthesized material can be considered as promising support for an anode in ADEFC. Graphical abstract: [Figure not available: see fulltext.]
Keywords: Alkaline direct ethanol fuel cell; Ethanol oxidation reaction; Graphene; Palladium